Application of the mineral processing methods in recycling the waste printed circuit boards - Magdalinović Srđana; Dimitrijević Silvana; Ivanović Aleksandra; Petrović Sanja; Krstić Slađana (Mining and Metallurgy Engineering Bor)
Development of the modern society has resulted in the production of various electronic equipment that becomes obsolete very quickly. This outdated equipment has been dumped on the landfills for many years. Electronic waste contains a significant amount of useful elements, so it represents a real resource for valorization. The presence of harmful elements classifies it as a hazardous waste, why a disposal in a specific area with special conditions is necessary. On the other hand, the massive exploitation of primary deposits has led to their depletion, creating an escalating demand for the new exploitation and concentration methods. Development of the recycling methods for such material is necessary from an economic and ecological point of view. Waste printed circuit boards can conditionally be viewed as a complicated mineral raw material. In mining, a methodology has been developed by which samples are tested to determine the concentration procedure. The same or similar approach is used during recycling. In this paper, an overview of the preparation methods of mineral raw materials that can be or are used in the recycling of waste printed circuit boards was carried out.